A Review of Fish Anomalies in Türkiye’s Waters - İsmail Reis; Sercan Yapıcı; Hasan Cerim; Özgen Yılmaz (Aquatic Sciences and Engineering)
In recent years, anomaly studies have increased in number, covering both individual cases and their effects on natural populations and farmed species. However, in the literature review, no current study has been found to compile the types and cases of anomalies encountered in species found in Türkiye’s waters. In the context of this review, 34 articles and symposium proceedings were found to belong to fish anomalies in Türkiye’s waters. In these studies, 62 individuals from 38 species and 20 families from different water bodies were detected to have at least one anomaly type that is included in this review. According to the literature, possible factors causing anomalies can be discussed under four general headings; environmental (anthropogenic factors, industrial activities, industrial chemicals, trace elements, pollution, light intensity, pesticide usage), biological (endocrine system, genetic, teratological cases, epigenetic, nutritional problems, parasitic or physiologic reasons, oxidative stress, pigment deficiency), ecological (attacked by carnivores, competition, changes in water parameters), and fishery-related (ghost fishing). This review also presents some possible causes of particular anomaly types in detail. It is thought that with the information provided, this review may establish an up-to-date basis for future studies.